Coordination of Eu3+ ions in siliceous nanohybrids containing short polyether chains and bridging urea cross-links - De Zea Bermudez, V.; Sá Ferreira, R. A.; Carlos, L. D.; Molina, C. [UNESP]; Dahmouche, K. [UNESP]; Ribeiro, Sidney José Lima [UNESP] (American Chemical Society (ACS), 2001)
Infrared and photoluminescence spectroscopies have been used to investigate the local environment of the Eu3+ ions in luminescent sol-gel derived materials-di-ureasils-based on a hybrid framework represented by U(600). This host is composed of a siliceous backbone grafted, through urea cross-links, to both ends of polymer segments incorporating 8.5 oxyethylene repeat units. The active centers have been introduced as europium perchlorate, Eu(ClO4)3. Samples with compositions n = 232, 62, 23, 12, and 6 (where n denotes the ratio of (OCH2CH2) moieties per lanthanide ion) have been examined. The combination of the information retrieved from the analysis of characteristic bands of the FTIR spectra-the perchlorate and the Amide I/Amide II features-with that obtained from the photoluminescence data demonstrates that at compositions n = 232 and 62 the anions are free, whereas the Eu3+ ions are complexed by the heteroatoms of the polyether chains. At higher salt concentration, the cations are bonded, not only to the ClO4 - ions, but also to the ether oxygen atoms of the organic segments and to the carbonyl oxygen atoms of the urea linkages. The dual behavior of U(600) with respect to cation coordination has been attributed to the presence in this nanohybrid of strong hydrogen-bonded urea-urea structures, which, at low salt content, cannot be disrupted, thus inhibiting the formation of Eu3+-O=C(urea) contacts and promoting the interaction between the lanthanide ions and the (OCH2CH2) moieties. The present work substantiates the claim that the activation of the coordinating sites of the di-ureasil framework can be tuned by varying either the guest salt concentration at constant chain length or the length of the.organic segments at constant salt concentration. This relevant property opens challenging new prospects in the fields of application of this class of hybrids. © 2001 American Chemical Society.
Keywords: Europium perchlorate; Heteroatoms; Siliceous nanohybrids; Atoms; Chemical bonds; Composition; Crosslinking; Crystal atomic structure; Europium compounds; Fourier transform infrared spectroscopy; Nanostructured materials; Photoluminescence; Polyethers; Sol-gels; Urea; Silicon compounds